Pengaruh Green Product dan Green Advertising terhadap Minat Beli Gen Z pada Produk Vegan Base - Maulida Fitria; Yuliana Riana Prasetyawati; Alvidiani Agustina Damanik (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The development of the beauty industry in Indonesia is projected to increase every year. One of the factors driving this development is the rise in consumption and use of cosmetics among Indonesian society. The National Waste Management Information System (SIPS) reported that in 2022 there were 35 million tonnes of waste, with the beauty industry contributing 6.8 million tonnes, 70% of which was not properly managed. This situation raises concerns about the welfare of the global ecosystem and encourages sustainability efforts across various business sectors. BASE is one of the companies that applies the green beauty concept through vegan products, environmentally friendly production processes, and several green movement initiatives. This study aims to measure the influence of green product and green advertising on the purchase intention of Generation Z in DKI Jakarta toward BASE’s vegan products. This research employs a quantitative method with a positivistic paradigm to measure the significance of influence and to test the hypotheses. The Theory of Consumption Value (TCV) serves as the theoretical foundation in understanding the underlying values that shape consumer purchase intention. Data from 100 respondents were processed using multiple linear regression analysis and hypothesis testing. The results indicate that green product and green advertising have a positive and significant simultaneous effect on purchase intention. These findings suggest that the implementation of green advertising by BASE as a marketing strategy, along with the green product concept that provides benefits for both users and the environment, contributes positively to increasing the purchase intention of Generation Z consumers.